Building a Conceptual Framework for E-Learning Based on Cloud Computing In Egyptian Universities (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2017)
In order to have an intelligent education, we have to make use of all modern education techniques. One of these techniques is the integration of information and communication technologies in education according to the global trend. In other words, to prepare a creative environment using means of existing web tools, techniques, and services to provide Browser-Based-Application. Nowadays Arab countries have a big interest in E-learning techniques and put it into the form of services within Services Oriented Architecture Technique (SOA), and mixing its input and outputs within the components of the Education Business Intelligence and enhance it to simulate reality by educational virtual worlds. This paper presents an idea about tools, instruments, techniques to enhance the educational process in the way that it could reach maximum uses of intelligent education modern technique.